Characterization of Heavy Metal Ions Removal from Water by Improved Cuttlebone Powder with Magnetic Fe3O4 Nanoparticle as a Bioadsorbent - Aida Didaran; Mahnaz Sadat Sadeghi; Parisa Nejatkhah Manavi; Mohammad Rabbani (Global Challenges)
Abstract Scientists are constantly striving to develop improved methods for reducing or eliminating the discharge of harmful heavy metals into drinking water sources and the environment. In light of this, this study investigates the potential of utilizing a naturally available and sustainable bio‐waste material, Sepia pharaonis cuttlebone Powder (SCP), as an exceptionally effective adsorbent for the adsorption of Ni (II), Pb (II), Cu (II), and Fe (II) ions. SCP is also characterized by Fourier‐transform infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Xray diffraction (XRD), and Energy dispersive Xray (EDX) analysis. The results reveal that the highest absorption values for Ni (II), Cu (II), and Fe (II) ions are observed at pH 8, while Pb (II) ions exhibit the highest absorption at pH 4. The absorption percentage of the ions displays an increasing trend with the amount of SCP used, as well as with contact time and magnetizing SCP duration. Additionally, the addition of Fe3O4 to SCP significantly improves the absorption rate of the samples. Both Langmuir and Freundlich adsorption models are found to fit the experimental data well. Overall, SCP, with or without Fe3O4 nanoparticles, shows great promise for water remediation processes by effectively removing heavy metals.